Richard Wagner and the Jews - Brener, Milton E. (McFarland & Company, 2006)
"The contradictions between Wagner's antipathy toward the amorphous entity "The Jews" and his genuine friendships with individual Jews are the subject of this book. Drawing on sources, including his autobiography and diary and the diaries of his second wife, this treatment of Wagner's anti-Semitism is the first to place it in perspective with his life and work"--Provided by publisher.